The Role of Pesantren and Its Literacy Culture in Strengthening Moderate Islam in Indonesia - Ali, Ali Muhdi; Fachrizal Halim (Edukasia Islamika : Jurnal Pendidikan Islam, 2023)
This study explores the strategic role of pesantren in promoting religious moderation  through the cultivation of a literacy culture. Amid rising concerns over radicalism fueled by  weak religious understanding and digital misinformation, pesantren emerges as resilient institutions fostering comprehensive Islamic learning grounded in textual literacy. The  research aims to analyze the motivations behind literacy practices, the development models  applied, the structural and cultural efforts by pesantren, and the contributions of students  and alumnae in spreading moderate Islamic values. Through a qualitative approach and  descriptive method, data were collected via observation, interviews, and document analysis  at Pesantren Nurul Ummah Yogyakarta. The findings reveal five dominant literacy  motivations: theological drive, kyai role modeling, academic obligations, personal interest,  and economic incentives. Literacy practices are institutionalized through both individual and  group habituation models. Pesantren support these initiatives structurally (e.g., through  curricula and publishing bodies) and informally (e.g., by promoting mutala’ah and media  engagement). The students and alumni have contributed significantly to the intellectual  Islamic discourse via publications, teaching, and digital media. This study confirms that  pesantren-based literacy development is pivotal to building a moderate, peaceful, and  inclusive Islamic civilization in Indonesia.